Servant Leadership as an Islamic Ethical Practice: Evidence from Public Secondary School in Kwara State, Nigeria - Mubarak Oluwatoyin Lawal; Safa Alrumayh; Faza Azkia (International Tatho Academics, 2026)
This study was carried out on servant leadership as an islamic ethical practice: evidence from public secondary schools in Kwara state, Nigeria. The study was guided by two purposes with two research questions. The research design that was used for this study was descriptive survey of the correctional-type method. The population of the study consisted of 8,085 respondents from public senior secondary schools. The sample size was determined using Krejie and Morgan, in which 278 was thereby chosen. Purposive and simple random sampling techniques were used to select the respondents in public senior secondary schools. A questionnaire was used by the researcher to elicit information from the concerned respondent, structured on a 4-point Liker rating scale. All the research questions were analysed using descriptive statistics of mean, standard deviation, frequency count and ranking order. The instrument was validated by my supervisor and two experts in the department of Education Management and Counselling at Al-Hikmah University. The reliability of the instrument was determined with Cronbach alpha at 0.71 and 0.80. The findings indicate that implementing servant leadership in schools aligns closely with Islamic ethical principles of responsibility, care, and service, demonstrating that these values can positively influence teachers’ job performance. One of the recommendations of this study is that the school administrators should organize regular training programs for principals that focus on enhancing servant leadership skills.